Abundance, biomass and distribution of demersal fish of the Caribbean Sea of Central América - Benavides-Morera, Rosario (2019)
A total of 96 sampling points were analyzed on board the B/O Miguel Oliver from January 3 to February 3, 2011. At each sampling point, trawling operations were carried out using a Lofoten network. The trawls of 30 minutes each were performed in 25 equidistant transects and divided into strata according to local depth, up to a maximum of 1500 m. A total of 142 species of bony and cartilaginous fish (n = 28074) belonging to 73 different families were found and analyzed. Relative abundance, biomass and catch frequency were determined. Antigoniacombatia showed the highest abundance (58.5%), Centrophorusgranulosus reported the most representative biomass in the study (10.9%), and Nezumiaaequalis was the most frequent species (32.6%). In addition, the spatial distribution in possible assemblages of the fish as a response to depth was studied. The cluster analysis (Mantel test r = 0.86; p <0.05), nonparametric spatial distribution analysis (NMDS) and similarity analysis (ANOSIM) provide sufficient evidence that species were found to be aggregated into spatial patterns with respect to the depth gradient.